Putusan Mahkamah Konstitusi dalam Pengelolaan Energi dan Sumber Daya Mineral dalam Perspektif Teori Sistem Hukum - Shera Cipta Ramdini (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
The Constitutional Court has decided the case filed by the Governor of East Java and the DPRD of East Java Province in case Number 11/PUU-XIV/2016. This decision became one of the landmark decisions of the Constitutional Court. The aim of this research is to find out and analyze the decisions of the Constitutional Court regarding the management of energy and mineral resources in Indonesia. This research method uses a normative juridical method with a statutory approach. The results of the research, Constitutional Court Decision Number 11/PUU-XIV/2016 have provided legal certainty regarding the regulation of the authority to administer geothermal energy for indirect use, including the authority to grant permits to the Central Government. In subsequent developments, geothermal regulation is regulated in the Job Creation Law which was declared formally conditionally unconstitutional based on Constitutional Court Decision Number 91/PUU-XVIII/2020. Legal system theory as an analytical tool functions to dissect factors relevant to the management of energy and mineral resources.